Comparison of vaccination schedules for foot-and-mouth disease among cattle and sheep in Mongolia - Ulziibat, Gerelmaa; Raizman, Eran; Lkhagvasuren, Amarsanaa; Bartels, Chris J. M.; Oyun-Erdene, Orgikhbayar; Khishgee, Bodisaikhan; Browning, Clare; King, Donald P.; Ludi, Anna B.; Lyons, Nicholas A. (Frontiers in Veterinary Science, 2023)
Vaccines are a critical tool for the control strategy for foot-and-mouth disease (FMD) in Mongolia where sporadic outbreaks regularly occur. A two-dose primary vaccination course is recommended for most commercial vaccines though this can be logistically challenging to deliver among nomadic pastoralist systems which predominate in the country. Although there is evidence that very high potency vaccines can provide prolonged duration of immunity, this has not been demonstrated under field conditions using commercially available vaccines. This study compared neutralizing titres to a O/ME-SA/Panasia strain over a 6-month period following either a two-dose primary course or a single double-dose vaccination among Mongolian sheep and cattle using a 6.0 PD50 vaccine. Titers were not significantly different between groups except in sheep at six-months post vaccination when the single double-dose group had significantly lower titers. These results indicate the single double-dose regimen may be a cost-effective approach for vaccination campaigns supporting FMD control in Mongolia.